Physical sport practice on women's free time - M. E. García; A. I. Hernández; A. Oña; J. F. Godoy; S. Rebollo (Asociación Española de Ciencias del Deporte, 2010)
The actual work has the aims: to know the availability of the free time, type of activities that they perform, the attitudes, motivations and behaviour to the physical-sportive practice of the free time in the Granada women, establishing the distinguishing features according to the place of residence, professional level and income per capital. All of them treated through a quantitative methodology, using the following techniques: the survey -through a questionnaire used by trained interviewers- and documentary observation. Sample error assumed 3% and a level of confidence about 95.5%, being used the survey technique of poliétapico "conglomerate". Data analysis techniques used have been quantitative, made by computer programming with SPSS/PC+ (V5.2), showing descriptive analysis of the different variable created, just as inferential analysis with the corresponding contingency tables, the Pearson index and the meaning level. KEY WORDS: Women, physical sport practice, free time, behavior.